The Role Of Farobi's "City Of Noble People" In The Spirituality Of Young People - Lutfullayev Abduvali Abdunabiyevich; Mehrochev Barot Botir o’g’li; Ergashov Yashnar Istam o’g’li; Utayev Aziz Toyir o’g’li (International Journal on Orange Technologies, 2021)
According to Farobi, human society is made up of different peoples, who differ from each other in language, customs, countries, and characteristics. The task of the Farobi state is to lead to happiness. This is achieved through science and good morals. According to him, “A good society and a good city (state) will be such that everyone from the population of this country will be engaged in a profession. "People will be truly free. They will have all kinds of good habits and pleasures." Faroobi is the king who leads such a noble community, and he also makes certain demands on the leaders. He must always take care of the solution, be able to put the interests of others in his own interests. The leader or group of managers of such a team must have an important golden quality